2020
DOI: 10.17816/1681-3456-2020-19-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined physical therapy for diabetic angiopathy

Abstract: Background. The problem of diabetic angiopathy is characteristic of countries even with a high level of development of medicine. The high frequency of complications of diabetes with high biological and social significance determines the need for their correction. The purpose of the work was to increase the effectiveness of rehabilitation treatment for patients with diabetic angiopathy through the combined use of therapeutic exercises and functional electrical stimulation of the lower extremities. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies conducted so far [92,[96][97][98][99][100][101] have demonstrated the effectiveness of the abovementioned physical therapies in reducing the extent of ischemic foot ulcers and improving limb blood supply [92,[97][98][99][100][101] in individuals with DM.…”
Section: Physicalmentioning
confidence: 99%
“…Studies conducted so far [92,[96][97][98][99][100][101] have demonstrated the effectiveness of the abovementioned physical therapies in reducing the extent of ischemic foot ulcers and improving limb blood supply [92,[97][98][99][100][101] in individuals with DM.…”
Section: Physicalmentioning
confidence: 99%
“…Diabetes incidence is increasing worldwide [5]: the population affected by this disease triplicated in the last 40 years [6], and it keeps on growing [7]. Diabetes-associated conditions affect multiple organs and organ systems, resulting in polyneuropathy [8], angiopathy [9], infections [10], nephropathy [10], dementia [11], cardiovascular complications [12], lower limb amputation [13], and blindness [14]. These phenomena are often irreversible and accompanied by a structural and functional impairment of the tissue microcirculation [15].…”
Section: Introductionmentioning
confidence: 99%